High frequency of Paracoccidioides brasiliensis infection in armadillos (Dasypus novemcinctus): an ecological study - Bagagli, E.; Franco, M.; Bosco, SDM; Hebeler-Barbosa, F.; Trinca, L. A.; Montenegro, M. R. (Taylor & Francis Ltd, 2003)
The fungus Paracoccidioides brasiliensis has been isolated from nine-banded armadillos (Dasypus novemcinctus) in different regions where paracoccidiodomycosis (PCM) is endemic. The link between PCM and these animals has provided the first valuable clue in the effort to elucidate the ecological niche of P. brasiliensis. The present study was aimed at correlating P. brasiliensis infection in armadillos with local ecological features and, if possible, the presence of the fungus in the soil in the Botucatu hyperendemic area of PCM. In this region the mean temperature ranges from 14.8 to 25.8degreesC and the annual average precipitation is 1520 mm. The sites where 10 infected animals (positive group) were collected were studied and compared with the sites where five uninfected animals were found. The occurrence of the fungus in soil samples collected from the positive armadillos' burrows and foraging sites was investigated by the indirect method of animal inoculation. Environmental data from the sites of animal capture, such as temperature, rainfall, altitude, vegetation, soil composition, presence of water and proximity of urban areas, were recorded. All 37 soil samples collected from the sites had negative fungal cultures. Positive animals were found much more frequently in sites with disturbed vegetation, such as riparian forests and artificial Eucalyptus Or Pinus forests, in altitudes below 800 m, near water sources. The soil type of the sites of positive animals was mainly sandy, with medium to low concentrations of organic matter. The pH was mainly acidic at all the sites, although the concentrations of aluminum cations (H+Al) were lower at the sites where positive animals were found. Positive armadillos were also captured in sites very close to urban areas. Our data and previous studies indicate that P. brasiliensis occurs preferentially in humid and shady disturbed forests in a strong association with armadillos.
Keywords: armadillos; Dasypus novemcinctus; ecology; Paracoccidioides brasiliensis; paracoccidioidomycosis